Effect of pore geometry on properties of high-temperature oxidized additively manufactured magnesium scaffolds - Chaoxin Wang; Shuyuan Min; Jinge Liu; Bingchuan Liu; Bo Peng; Caimei Wang; Xiaolin Ma; Peng Wen; Yufeng Zheng; Yun Tian (Journal of Magnesium and Alloys)
Only a few studies have examined how pore geometry affects the mechanical characteristics, biological behavior, and degradation of additively manufactured biodegradable porous magnesium. In this work, the effects of pore geometry on mechanical qualities, degradation, and biological behavior were investigated using three typical porous architectures with the same porosity. The porous structures were found to satisfy bone tissue engineering requirements because they had sufficient degradation resistance and tunable compressive characteristics. All three types of magnesium alloy scaffolds exhibited good biocompatibility. Additionally, the magnesium alloy porous structures influenced the magnesium scaffold material degradation rate and the surrounding environment, impacting the osteogenic differentiation of bone mesenchymal stem cells and bone tissue regeneration. This work offers conceptual support for optimizing pore geometry to alter the mechanical and degradable characteristics of additively manufactured porous magnesium to meet therapeutic demands.